The Potential Role of Placenta Morphological, Cytogenetic and Histological Findings in Fetal Phenotype Modeling: A Case Report with Unanswered Questions - Strautmane, Estere; Korņejeva, Liene; Ločmele, Dzintra; Riekstiņa, Marta; Bokučava, Diāna; Vedmedovska, Natālija (Acta medica Lituanica, 2025)
Placental abnormalities significantly contribute to fetal mortality. Maternal vascular underperfusion emerges as the prevailing diagnosis. At the same time, genomic alterations within the placenta might play a role in the development of placental dysfunction. We present a case report of a 24-year-old primigravida with an uneventful medical history, admitted at 21 weeks and 2 days gestation. Despite a low risk for typical trisomies, a high risk for preeclampsia and fetal growth restriction (FGR) was recognized in the first trimester. Anhydramnios, abnormal placental morphology, retrochorial and retromembranous hematomas were observed, prompting the termination of pregnancy (TOP). Histological examination revealed multiple placental abnormalities, while the fetus displayed normal anatomy and phenotype. Discussion encompasses the varied manifestations of histopathological findings, and potential associations with adverse pregnancy outcomes. Our case underscores the importance of meticulous evaluation and multidisciplinary collaboration in managing pregnancies with placental anomalies. Further research is crucial to discern the intricate relationship between placental cytogenetics, morphology, and pregnancy outcomes, thus facilitating better clinical management and counseling strategies.